2018
DOI: 10.1111/opec.12125
|View full text |Cite
|
Sign up to set email alerts
|

Oil price cycles, fiscal dominance and countercyclical monetary policy in Iran

Abstract: The mission of monetary policy is to conduct countercyclical policy, however, this is not a universally practiced norm. Pro‐cyclical fiscal and monetary policies during boom periods have often been observed in developing countries and tend to amplify the impact of positive commodity price shocks. The consequence is strengthening of domestic inflationary pressures and appreciation of the exchange rate. This paper examines counter‐cyclicality of monetary policy and the role of fiscal policy in this regard. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another study in Iran found that using the volunteer force for the Iranian government saved more than $ 4 per dollar 30 . The reason for the decrease in this rate in recent years is the devaluation of Iran's currency and the consequent rise in prices for various services such as food and transportation 31 . On the other hand, wages in Iran have not increased in proportion to the devaluation of the currency 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Iran found that using the volunteer force for the Iranian government saved more than $ 4 per dollar 30 . The reason for the decrease in this rate in recent years is the devaluation of Iran's currency and the consequent rise in prices for various services such as food and transportation 31 . On the other hand, wages in Iran have not increased in proportion to the devaluation of the currency 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies highlight the importance of fiscal deficit and institutional arrangements that adversely affect central bank's independence (e.g. Alavirad and Athawale, 2005;Kia, 2006;Samimi and Jamshidbaygi, 2011;Naini and Naderian, 2019;Mazarei, 2020). The potential impact of sanctions on Iran's macroeconomic condition is also a unique factor (Kandil and Mirzaie, 2021); their effects on inflation are explored in several studies.…”
Section: Inflation In Iranmentioning
confidence: 99%
“…Other studies highlight the importance of fiscal deficit and institutional arrangements that adversely affect central bank's independence (e.g. Alavirad and Athawale, 2005; Kia, 2006; Samimi and Jamshidbaygi, 2011; Naini and Naderian, 2019; Mazarei, 2020).…”
Section: Inflation In Iranmentioning
confidence: 99%
“…Yang et al (2021) investigated the impact of five global financial market uncertainty on the price dynamics of Shanghai Crude oil futures and find China's crude oil futures volatility, including intraday volatility and its components, moves tightly with all the global financial uncertainties. Crude oil price volatility is cyclical (Naini et al, 2017). Therefore, the risk of financial cycle volatility also affects crude oil prices.…”
Section: Review Of Literaturementioning
confidence: 99%